2021
DOI: 10.1073/pnas.2023749118
|View full text |Cite
|
Sign up to set email alerts
|

Precapillary sphincters and pericytes at first-order capillaries as key regulators for brain capillary perfusion

Abstract: Rises in local neural activity trigger local increases of cerebral blood flow, which is essential to match local energy demands. However, the specific location of microvascular flow control is incompletely understood. Here, we used two-photon microscopy to observe brain microvasculature in vivo. Small spatial movement of a three-dimensional (3D) vasculature makes it challenging to precisely measure vessel diameter at a single x–y plane. To overcome this problem, we carried out four-dimensional (x–y–z–t) imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 65 publications
5
50
1
Order By: Relevance
“…injection or incubation of tissue with AlexaFluor 633 hydrazide ( Shen et al, 2012 ), but its role in microvascular regulation remains understudied. Recently, however, it has been used to identify intracortical arterioles in which endothelial caveolae were found to be critical players in neurovascular coupling ( Chow et al, 2020 ), and was found around precapillary sphincters branching off penetrating arterioles that regulate blood flow and pressure into the cortical capillary network ( Grubb et al, 2020 ; Zambach et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…injection or incubation of tissue with AlexaFluor 633 hydrazide ( Shen et al, 2012 ), but its role in microvascular regulation remains understudied. Recently, however, it has been used to identify intracortical arterioles in which endothelial caveolae were found to be critical players in neurovascular coupling ( Chow et al, 2020 ), and was found around precapillary sphincters branching off penetrating arterioles that regulate blood flow and pressure into the cortical capillary network ( Grubb et al, 2020 ; Zambach et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the same group found much more variable timings in neocortex of ketamine-medetomidine anaesthetized or awake mice, with capillaries or arterioles each being faster on some occasions ( Rungta et al, 2021 ), and in both these reports, mid-capillary dilations were very small (though these data conflate responders and non-responders, unlike some other studies, Hall et al, 2014 ; Shaw et al, 2021 ). Precapillary sphincters, where studied, have often shown larger dilations, as a proportion of their diameter, than adjacent arterioles and capillaries ( Grubb et al, 2020 ; Zambach et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, the decrease in MCAv observed in med-highs during hyperventilation despite scarce changes in ABP, could be sustained by the sensitivity of their vessels muscle cells to blood pressure. The preferential effect of NO on precapillary sphincters and pericytes rather than on smooth muscle cells [67] may have contributed to the observed changes in MCAv. The lack of significant correlation between ΔMCAv and ΔPETCO2 occurring in both groups during rebreathing may be due to CO2 ceiling effect.…”
Section: Correlational Analysesmentioning
confidence: 96%
“…However, once again, it is at the capillary level that the astrocyte foot processes have the greatest influence [ 4 , 8 ]. The question of whether the capillaries themselves are responsible for the autonomous increase or decrease in the size of the vascular bed draws attention to the function of the pericytes that reside here [ 24 , 25 , 26 , 27 , 28 ]. It has long been reported that pericytes contain actin filaments, which have a contractile effect.…”
Section: Functional Hyperemia At the Capillary Levelmentioning
confidence: 99%
“…Regulation of the CBF is mainly mediated by vascular smooth muscle contraction and relaxation at the level of the upstream arterioles. However, it has been pointed out that pericytes may be involved in the dilatation and contraction of microvessels even at the capillary level [ 24 , 25 , 26 , 27 , 28 ]. In addition to pericyte regulation, the capillary bed size may also be actively regulated by an increase or decrease in water content in the Virchow–Robin space [ 29 , 30 , 31 ], the space between the astrocytic end feet and the outer surfaces of the microvessels.…”
Section: Introductionmentioning
confidence: 99%